The Immune System's Role in the Consequences of Mild Traumatic Brain Injury (Concussion) - Verboon, Laura N.; Patel, Hiren C.; Greenhalgh, Andrew D. (Frontiers in Immunology, 2021)
Mild traumatic brain injury (mild TBI), often referred to as concussion, is the most common form of TBI and affects millions of people each year. A history of mild TBI increases the risk of developing emotional and neurocognitive disorders later in life that can impact on day to day living. These include anxiety, depression, as well as neurodegenerative conditions such as chronic traumatic encephalopathy (CTE) and Alzheimer’s disease (AD). Actions of brain resident or peripherally recruited immune cells is proposed to be a key regulator across these disease and mood disorders. Here, we will assess the impact of mild TBI on brain and patient health, and the recent evidence for immune cell involvement in its pathogenesis.